1978
DOI: 10.1063/1.436648
|View full text |Cite
|
Sign up to set email alerts
|

Polarized resonance Raman spectra of hexahalide complexes of transition metals: The effect of electronic degeneracy on the polarization of vibrational Raman scattering

Abstract: Polarized vibrational resonance Raman spectra have been measured for eight hexahalide complexes of transition metals, low-spin d4 OsCl62−, OsBr62−, and low-spin d5 IrCl62−, IrBr62−, and low-spin d6 PdCl62−, PtCl62−, PtBr62−, and PtI62−. Polarization anomaly due to asymmetric Raman tensor was found for the d5 complexes, whereas such was not observed in the cases of the d4 and d6 complexes. The result is analyzed on the basis of a symmetry consideration in vibronic space. Electronic and/or vibrational degeneracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…These results are in line with the observations noted for K 2 OsX 6 compounds. [30,34,35] The ambient, pH, and thermal stabilities of these materials are analyzed, and the data are shown in Figure 2. The XRD plots (Figure 2a-c and Figures S4 and S5, Supporting Information) show diffraction patterns of the materials kept in ambient conditions for ten months and they are similar to as-synthesized samples without any impurity phases.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in line with the observations noted for K 2 OsX 6 compounds. [30,34,35] The ambient, pH, and thermal stabilities of these materials are analyzed, and the data are shown in Figure 2. The XRD plots (Figure 2a-c and Figures S4 and S5, Supporting Information) show diffraction patterns of the materials kept in ambient conditions for ten months and they are similar to as-synthesized samples without any impurity phases.…”
Section: Resultsmentioning
confidence: 99%
“…A recent report on the [IrBr 6 ] 2– crystal structure with a tetra­( para -tolyl)­stibonium cation grown from dimethyl sulfoxide concluded that the ion was indeed octahedral, with an average Ir–Br bond length of 2.4785 ± 0.0071 Å . In addition, resonance Raman measurements performed on the [IrBr 6 ] 2– ion in solution revealed only three Raman-active stretching modes consistent with an octahedral symmetry. …”
mentioning
confidence: 94%